An Investigation into Cybercrime Awareness and Security Measures - Parul Grag; Jyoti Gaur; Ankit Goel; Rajeev Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
The widespread adaptation of the internet has integrated it into the daily routines of a vast majority of individuals for various transactions. Correspondingly, the user base of the internet has experienced significant growth, paralleled by a rise in cybercrimes. Cybercrime, executed through computers and networks, poses a persistent and escalating threat across professional and personal fields. The arising of the internet has transformed traditional crimes into new forms. This research aims to raise awareness about contemporary cybercrimes and promote heightened cybersecurity measures. Furthermore, it endeavours to examine the levels of computer crime alertness among inter web users of various age groups and educational backgrounds. Utilizing a Linear predictive model, this study analyses both objectives. The findings reveal a correlation between respondents’ age groups and educational qualifications. Therefore, it is incumbent upon all internet users to remain vigilant regarding cybercrime and cybersecurity, as well as to actively foster awareness among others.